The Comparative Toxicogenomics Database: update 2017. Issue Volume 45:Issue D1(2017) (19th September 2016) - Davis, Allan Peter; Grondin, Cynthia J.; Johnson, Robin J.; Sciaky, Daniela; King, Benjamin L.; McMorran, Roy; Wiegers, Jolene; Wiegers, Thomas C.; Mattingly, Carolyn J.
Abstract: The Comparative Toxicogenomics Database (CTD; http://ctdbase.org/ ) provides information about interactions between chemicals and gene products, and their relationships to diseases. Core CTD content (chemical-gene, chemical-disease and gene-disease interactions manually curated from the literature) are integrated with each other as well as with select external datasets to generate expanded networks and predict novel associations. Today, core CTD includes more than 30.5 million toxicogenomic connections relating chemicals/drugs, genes/proteins, diseases, taxa, Gene Ontology (GO) annotations, pathways, and gene interaction modules. In this update, we report a 33% increase in our core data content since 2015, describe our new exposure module (that harmonizes exposure science information with core toxicogenomic data) and introduce a novel dataset of GO-disease inferences (that identify common molecular underpinnings for seemingly unrelated pathologies). These advancements centralize and contextualize real-world chemical exposures with molecular pathways to help scientists generate testable hypotheses in an effort to understand the etiology and mechanisms underlying environmentally influenced diseases.